বিনয় সরকারের বৈঠকে : বিংশ শতাব্দীর বঙ্গ-সংস্কৃতি, দ্বিতীয় ভাগ - মুখোপাধ্যায়, হরিদাস
Author's interviews with Benoy Kumar Sarkar, 1887-1949, Indic scholar and educationist, on various Indian social topics.